2010
DOI: 10.1002/ijc.25322
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer risk in relation to antidepressant medication use

Abstract: Laboratory studies suggest that antidepressants affect the risk of some cancers, including colorectal cancer. To investigate whether selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs) are associated with colorectal cancer risk, we conducted a case-control study among enrollees of an integrated healthcare delivery system in Washington State. Cases were first diagnosed with invasive colorectal cancer between 2000 and 2003; controls were randomly selected from Group Health enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
1
45
1
Order By: Relevance
“…We then reported that FLX could also reduce pre-existent colon preneoplastic lesions [64] . Our findings suggested that FLX takes the carcinogen-induced preneoplastic changes under control by reducing epithelial proliferation [38,56,60,61,64,65] . Besides the fact that FLX treatment reduced dysplasia and preneoplastic angiogenesis, decreasing the epithelial and subepithelial proliferation [64,65] , our unpublished dataset further suggests that by suppressing the NF-ÎșB nuclear activity, through increased expression of cytoplasmic NF-ÎșB-inhibitor IÎșB-α and IÎșB-ÎČ proteins, FLX reduced c-Myc expression and then stromal proliferation (Figures 2 and 3).…”
Section: Flx Reduces Preneoplastic Lesions Acting On Colonic Microenvmentioning
confidence: 66%
See 1 more Smart Citation
“…We then reported that FLX could also reduce pre-existent colon preneoplastic lesions [64] . Our findings suggested that FLX takes the carcinogen-induced preneoplastic changes under control by reducing epithelial proliferation [38,56,60,61,64,65] . Besides the fact that FLX treatment reduced dysplasia and preneoplastic angiogenesis, decreasing the epithelial and subepithelial proliferation [64,65] , our unpublished dataset further suggests that by suppressing the NF-ÎșB nuclear activity, through increased expression of cytoplasmic NF-ÎșB-inhibitor IÎșB-α and IÎșB-ÎČ proteins, FLX reduced c-Myc expression and then stromal proliferation (Figures 2 and 3).…”
Section: Flx Reduces Preneoplastic Lesions Acting On Colonic Microenvmentioning
confidence: 66%
“…In patients, FLX treatment was reported to reduce the risk of colon cancer to almost 50% [60] . Chubak et al [61] also observed that FLX reduced the risk of colon cancer in humans, while one meta-analysis study suggested that FLX does not act on colon cancer [62] . Studies with animal models support the idea of FLX reducing colon cancer incidence in different animal models, such as carcinogen induced preneoplastic lesions and tumors in rats and mice, and xenograft tumors in immunosuppressed rats [38,[63][64][65] .…”
Section: Flx Takes Energy Generation Un-der Control To Reduce Malignamentioning
confidence: 99%
“…Conflicting results of antidepressant use and de novo cancer risk have been reported [264][265][266][267][268][269][270]. A case-control study found no association between antidepressant use and breast cancer risk; a protective effect of paroxetine hydrochloride was observed in subjects who were not overweight [264].…”
Section: Antidepressant Usementioning
confidence: 99%
“…A nested case-control study found a protective effect of SSRIs on the risk of lung cancer, but a non-significant elevated risk with tricyclic antidepressants; the authors attribute the potential effects to residual confounding [267]. A reduced risk of colorectal cancer was seen with antidepressant use [268,269]. The association between antidepressants and breast cancer and antidepressants and ovarian cancer are mixed in the preclinical and clinical data.…”
Section: Antidepressant Usementioning
confidence: 99%
See 1 more Smart Citation